Molecular confirmation and morphological reassessment of Udotea geppiorum (Bryopsidales, Chlorophyta) with ecological observations of mesophotic meadows in the Main Hawaiian Islands. Issue 2 (2nd April 2020) - Sauvage, Thomas; Ballantine, David L.; Peyton, Kimberly A.; Wade, Rachael M.; Sherwood, Alison R.; Keeley, Sterling; Smith, Celia
ABSTRACT: Udotea geppiorum is reported to form meadows in deep-water, soft sediment habitats in the Main Hawaiian Islands. The identification of the species, initially published as U. argentea in the archipelago, is revised and confirmed based on morphological assessment and comparative DNA sequencing with western Pacific specimens. Udotea geppiorum is fully corticated and newly shown to display discrete concentric segments arranged in a 'tongue and groove' manner, which are connected by medullary siphons running along the entire segment interface. Udotea geppiorum is phylogenetically nested among a cluster of Udotea spp. recently circumscribed within Udotea sensu stricto . This cluster of species is separate from the remainder of the family Udoteaceae, which includes several genera and Udotea spp. sensu lato that lack or exhibit incomplete cortication. Based on field observations conducted in O'ahu and Maui, U. geppiorum can be found from 20 m to > 90 m depth with a peak in abundance at mesophotic depths of 60–85 m, where it forms extensive meadows that support associated diversity.